State Neutrality, Business Elite and the Lack of Export Services Development in Chile: an Exploratory Qualitative Analysis - Lopez, Dorotea; Munoz, Felipe; Ahumada, José Miguel (Organizations and Markets in Emerging Economies, 2020)
The process of economic development implies, among other things, the expansion of exports beyond natural resources and towards more knowledge intensive sectors. However, a common situation in developing countries is the lack of an ‘entrepreneurial push’ from economic and political elites in order to diversify such exports. The Chilean economy is not an exception as it is still characterized by an export basket anchored in natural resources, regardless the consensus among society on the importance of diversifying the Chilean economy towards new industrial and service sectors, both beyond and within natural resources. This paper focuses on the causes of the absence of such an ‘entrepreneurial push’ towards export service sector in Chile and, through a qualitative exploratory analysis of elite perceptions, presents the predominant hypothesis among key stakeholders.